Competencies for Student Leadership Development in Doctor of Pharmacy Curricula to Assist Curriculum Committees and Leadership Instructors - Janke, Kristin K. (American Journal of Pharmaceutical Education, 2013)
Objective. To assist curriculum committees and leadership instructors by gathering expert opinion to define student leadership development competencies for pharmacy curricula. Methods. Twenty-six leadership instructors participated in a 3-round, online, modified Delphi process to define competencies for student leadership development in pharmacy curricula. Round 1 asked open-ended questions about leadership knowledge, skills, and attitudes. Round 2 grouped responses for agreement rating and comment. Round 3 allowed rating and comment on competencies not yet meeting consensus, which was prospectively set at 80%. Results. Eleven competencies attained 80% consensus or higher and were grouped into 3 areas: leadership knowledge, personal leadership commitment, and leadership skill development. Connections to contemporary leadership development literature were outlined for each competency as a means of verifying the panel’s work. Conclusions. The leadership competencies will aid students in addressing: What is leadership? Who am I as a leader? What skills and abilities do I need to be effective? The competencies will help curriculum committees and leadership instructors to focus leadership development opportunities, identify learning assessments, and define program evaluation.